Profil Miskonsepsi Siswa Kelas X di Sebuah SMA Swasta di Karanganyar - Liina, As Syaffa Al; Pitorini, Dewi Ekaputri; Salma, Safina; Nisa, Salis Khoirun; Prayitno, Baskoro Adi (JP (Jurnal Pendidikan) : Teori dan Praktik, 2018)
Penelitian ini bertujuan untuk mengetahui profil miskonsepsi siswa kelas X di sebuah SMA Swasta di Karanganyar pada materi fotosintesis dan respirasi tumbuhan. Penelitian ini menggunakan metode survei. Populasi penelitian adalah seluruh siswa SMA kelas X MIA. Teknik sampling menggunakan purposive random sampling dengan jumlah sampel sebanyak 25 siswa. Miskonsepsi diukur menggunakan tes pilihan ganda Science & Plant For School yang disertai Certainty of Response Index (CRI) pada konsep fotosintesis dan respirasi tumbuhan. Analisis data menggunakan analisis deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa persentase siswa yang mengalami miskonsepsi pada konsep Fotosintesis dan Respirasi Tumbuhan sebesar 41,6%, siswa yang tahu konsep sebesar 38% dan siswa yang tidak tahu konsep sebesar 20,4%. Abstract This study aims to determine the profile misconception of class X students in a private high school in Karanganyar of photosynthesis and plant respiration material. This study used survey meta-analysis. The study population is all high school students of X class MIA. The sampling technique uses purposive random sampling with the number of samples as much as 25Student. Misconceptions measured were measured using the Science & Plant For School multiple-choice test accompanied by the Certainty of Response Index (CRI) on the concept of photosynthesis and plant respiration. Data analysis used quantitative descriptive analysis. The results showed that the percentage of students who experienced misconceptions on the concept of photosynthesis and plant respiration 41.6%, students who know the concept of 38% and students who do not know the concept of 20.4%.